PENERAPAN TEKNIK PENILAIAN PADA PELAJARAN SENI MUSIK DI SMP NEGERI 4 KECAMATAN GUGUAK - Susy Lestary Ningsih; Idawati Syarif; Yos Sudarman (SENDRATASIK UNP, 2013)
Abstract   This article was aimed at describing the implementation of evalution technique in Arts and Music subject at SMP Negeri 4 Kecamatan Guguak. This was a qualitative research that used descriptive-analysis method. The result of the research indicated that the evaluation technique applied by the teacher  was only on cognitive and psychomotor aspects while the affective aspect was ignored. Thus,it was concluded that the evaluation done by the teacher did not run as it was expected.   Kata Kunci : teknik penilaian